2001
DOI: 10.1152/ajpregu.2001.281.5.r1426
|View full text |Cite
|
Sign up to set email alerts
|

PVN activation is suppressed by repeated hypoglycemia but not antecedent corticosterone in the rat

Abstract: The mechanism(s) underlying hypoglycemia-associated autonomic failure (HAAF) are unknown. To test the hypothesis that the activation of brain regions involved in the counterregulatory response to hypoglycemia is blunted with HAAF, rats were studied in a 2-day protocol. Neuroendocrine responses and brain activation (c-Fos immunoreactivity) were measured during day 2 insulin-induced hypoglycemia (0.5 U insulin x 100 g body x wt(-1) x h(-1) iv for 2 h) after day 1 hypoglycemia (Hypo-Hypo) or vehicle. Hypo-Hypo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
79
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 60 publications
16
79
2
Order By: Relevance
“…In one study, Shum et al (19) found that antecedent glucocorticoid administration had no discernable impact upon subsequent epinephrine responses to hypoglycemia. In another study, direct delivery of corticosterone into the hypothalamus also failed to blunt subsequent counterregulatory responses to hypoglycemia (20). From our lab, Flanagan et al (21) reported that antecedent glucocorticoid exposure actually augmented subsequent epinephrine responses to hypoglycemia, whereas antecedent CRH exposure suppressed the sympathoadrenal response.…”
Section: Discussionmentioning
confidence: 73%
“…In one study, Shum et al (19) found that antecedent glucocorticoid administration had no discernable impact upon subsequent epinephrine responses to hypoglycemia. In another study, direct delivery of corticosterone into the hypothalamus also failed to blunt subsequent counterregulatory responses to hypoglycemia (20). From our lab, Flanagan et al (21) reported that antecedent glucocorticoid exposure actually augmented subsequent epinephrine responses to hypoglycemia, whereas antecedent CRH exposure suppressed the sympathoadrenal response.…”
Section: Discussionmentioning
confidence: 73%
“…Despite the fact that we only exposed the rats to one episode of hypoglycemia and we waited 48 h for recovery, we still found significant blunting of epinephrine responses to hypoglycemia after a single episode of moderate hypoglycemia. This rodent model of HAAF is unique in that suppressed epinephrine responses are seen after a single episode of moderate hypoglycemia, rather than multiple episodes used in other models (Evans et al, 2001;Sivitz et al, 2001;Inouye et al, 2002;Flanagan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Variable effects on norepinephrine, glucagon, and corticosterone responses to hypoglycemia have been reported (Evans et al, 2001;Shum et al, 2001;Flanagan et al, 2003;De Vries et al, 2004). A recent report indicates that a single prolonged episode of moderate hypoglycemia does not significantly reduce the epinephrine response to subsequent hypoglycemic challenge (Paranjape and Briski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, neural pathways stimulated by hypoglycemia induce feeding behavior [2]. Hormone responses and symptoms of hypoglycemia tend to be blunted in DM patients treated with insulin, and it is likely that deficient responses to hypoglycemia result from recurrent severe hypoglycemia sustained over many years of insulin replacement [1] CNS mechanisms of autonomic and endocrine responses to hypoglycemia have been studied in dogs and in rodents, and these studies indicate participation of structures in brainstem as well as hypothalamus [3][4][5][6][7][8][9][10][11][12]. Although these animal studies have proven useful in elucidating aspects of neural circuitry underlying counterregulatory hormone secretion, symptom thresholds, per se, cannot be directly assessed in an animal model.…”
Section: Introductionmentioning
confidence: 99%